Anxiety and quality of life after first‐trimester termination of pregnancy: a prospective study. (19th September 2016) - Toffol, Elena; Pohjoranta, Elina; Suhonen, Satu; Hurskainen, Ritva; Partonen, Timo; Mentula, Maarit; Heikinheimo, Oskari
Abstract: Introduction: Possible effects of termination of pregnancy (TOP) on mental health are a matter of debate. Material and methods: We assessed anxiety and quality of life during a one‐year follow up after first‐trimester TOP using the State‐Trait Anxiety Inventory (STAI) Scale and EuroQoL Quality of Life Questionnaire (EQ‐5D, EQ‐VAS) in 742 women participating in a randomized controlled trial on early provision of intrauterine contraception. The measurements were performed before TOP, at 3 months and 1 year after TOP. Inclusion criteria were age ≥18 years, residence in Helsinki, duration of gestation <12 weeks, non‐medical indication for TOP, and approval of intrauterine contraception. The trial was registered with Clinical Trials [NCT01223521]. Results: When compared with baseline, the overall anxiety level was significantly lower and quality of life higher at 3 months and at 1 year. Reduction of anxiety and improvement of quality of life was especially evident ( p < 0.001) in the 58% of women reporting clinically relevant anxiety at baseline. High levels of anxiety at baseline, history of psychiatric morbidity and smoking predicted significantly greater risk of poorer quality of life and elevated level of anxiety during the follow up. Conclusions: TOP is associated with a significant overall reduction of anxiety and an improvement of quality of life among women undergoing it for non‐medical indications. High baseline anxiety, history of psychiatric morbidity and smoking are risk factors of persistently high levels of anxiety and poor quality of life after an induced abortion. These data are important when designing and providing post‐abortion care.